The influence of the post-isometric relaxation technique of the iliopsoas muscle on the functional abbreviation of the lower limb. Case study. - Puchalska-Sarna, Anna; Sarna, Michal; Touma, Victor; Touma, Joanna; Puchalski, Krzysztof (Technium BioChemMed, 2022)
The influence of the post-isometric relaxation technique of the iliopsoas muscle on the functional abbreviation of the lower limb. Case study. Introduction Leg length discrepancy (LLD) is an effect often described in the literature as uneven length of the lower limbs. It covers about 40-70% of the population and can exceed 2 cm of inequality in nearly 0.1%. Methody Material/Methody A woman of 40 years with a functional leg abbreviation (LLD), for a period of 6 weeks performed the technique of post-isometric relaxation of the hip-lumbar muscle. In the morning with a therapist, in the evening as self-therapy. Hipoteza: 1.Does the pir technician affect the elongation of a seemingly shortened leg? 2. What is the duration of the leg extension? Conclusion: 1.Unfortunately, the effect lasted up to two days after 6 weeks of therapy, after 2 days there was a return from before the therapy 2. The effect of hip-lumbar pir gave effects but unfortunately not permanent